2013
DOI: 10.1111/pce.12169
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate induction of the monoterpene linalool confers resistance to rice bacterial blight and its biosynthesis is regulated by JAZ protein in rice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 65 publications
(177 reference statements)
3
104
0
Order By: Relevance
“…Moreover, due to its relatively small and fully sequenced genome, its ease of transformation, accumulated wealth of genetic and molecular resources, and extensive synteny and collinearity with other cereals, rice is an excellent model for molecular genetic studies in monocots (Jung et al, 2008). Intriguingly, recent findings propose a conceptually different model for rice defense signaling that challenges the widely accepted dichotomy between the effectiveness of the SA and JA pathways and the overall infection biology of the invading pathogen (Yamada et al, 2012;De Vleesschauwer et al, 2013Riemann et al, 2013;Taniguchi et al, 2014). Perhaps most conspicuously, synergistic SA-JA interactions seem to prevail in rice and the two hormones are hypothesized to feed into a common defense pathway that can be effective against both hemibiotrophic and necrotrophic rice pathogens Tamaoki et al, 2013).…”
mentioning
confidence: 99%
“…Moreover, due to its relatively small and fully sequenced genome, its ease of transformation, accumulated wealth of genetic and molecular resources, and extensive synteny and collinearity with other cereals, rice is an excellent model for molecular genetic studies in monocots (Jung et al, 2008). Intriguingly, recent findings propose a conceptually different model for rice defense signaling that challenges the widely accepted dichotomy between the effectiveness of the SA and JA pathways and the overall infection biology of the invading pathogen (Yamada et al, 2012;De Vleesschauwer et al, 2013Riemann et al, 2013;Taniguchi et al, 2014). Perhaps most conspicuously, synergistic SA-JA interactions seem to prevail in rice and the two hormones are hypothesized to feed into a common defense pathway that can be effective against both hemibiotrophic and necrotrophic rice pathogens Tamaoki et al, 2013).…”
mentioning
confidence: 99%
“…[4][5][6][7][8] In addition, it has been revealed that JA treatment causes the accumulation of plant volatile compounds in rice. [9][10][11] Plant volatile compounds, such as terpenoids and C 6 volatiles, are emitted from microbe-infected or wounded plant sites, and are potential signal compounds that induce defenses against tissue damage from herbivores and plant pathogens. [12][13][14][15] In addition to the function as a signaling molecule, some volatile compounds have antimicrobial activities against plant pathogens.…”
mentioning
confidence: 99%
“…oryzae (Xoo) in rice. 11 Taken together, it is indicated that plant volatile compounds have an important role in stress and defense responses in plants. However, the function of individual volatiles in plant defense remains unclear.…”
mentioning
confidence: 99%
“…Release of a transcriptional activator such as MYC2 from repression by the JAZ protein interaction accelerates the expression of downstream genes, such as JA-inducible defenserelated genes (Wasternack and Hause 2013). These core components in JA signaling are conserved in rice as well (Cai et al 2014;Taniguchi et al 2014a;Ye et al 2012).…”
Section: Signaling Pathways Leading To the Phytoalexin Biosynthesis Mmentioning
confidence: 99%
“…Among these, OsCOI1a and OsJAZ8 were individually reported to be involved in jasmonate-mediated rice defense responses (Taniguchi et al 2014a;Taniguchi et al 2014b;Ye et al 2012). However, their roles in the production of rice phytoalexins have not been investigated.…”
Section: Signaling Pathways Leading To the Phytoalexin Biosynthesis Mmentioning
confidence: 99%